Students Metacognitive Strategies for Supporting Critical Thinking in Learning Speaking Discussion Text - ALFI MUHAMMAD, GAGAH (RETAIN : Journal of Research in English Language Teaching, 2019)
Abstrak Berpikir kritis menjadi hal penting di era pendidikan saat ini. Cara mengembangkan pemikiran kritis siswa diterapkan oleh banyak guru baik secara langsung maupun tidak langsung. Dalam pendidikan bahasa Inggris, berpikir kritis juga memainkan peran penting dalam pengembangan siswa dalam memahami pelajaran. Pemikiran kritis siswa memiliki peran besar dalam pengembangan keterampilan bahasa siswa. Namun, melihat banyak strategi pembelajaran metakognitif yang tersedia, itu membuat siswa sulit untuk mengembangkan pemikiran kritis mereka. Melihat hal ini, peneliti melakukan penelitian dengan tujuan menemukan strategi pembelajaran apa yang digunakan siswa untuk mendukung keterampilan berpikir kritis siswa. Tujuan lain dari penelitian ini adalah untuk mengeksplorasi alasan siswa dalam memilih strategi yang mereka sukai. Peneliti fokus pada siswa sekolah menengah dan peneliti menggunakan pendekatan kualitatif. Menurut para ahli, Inferencing memang merupakan strategi yang cukup sulit bagi siswa untuk diterapkan sehingga strategi tersebut hanya cocok untuk orang dewasa. Para ahli percaya bahwa dalam menerapkan strategi menyimpulkan perlu banyak latihan dan pelatihan untuk membantu peserta didik menerapkan strategi ini dalam mendukung pemikiran kritis mereka. Kata Kunci: berfikir kritis, strategi metakognitif, kemampuan berbicara, teks diskusi Abstract Critical thinking becomes an important thing in the current era of education. The way to develop students critical thinking is applied by many teachers both directly and indirectly. In English education, critical thinking also plays an important role in the development of students in understanding lessons. Students critical thinking have a big role in the development of students language skills. However, seeing the many metacognitive learning strategies that available, it make student difficult to develop their critical thinking. Seeing this, researchers conducted research with the aim of discovering what learning strategies students used to support students critical thinking skills. Another aim of this research is also to explore the reason of the students in choosing their preferred strategy. The researcher focused on high school students and the researchers used a qualitative approach. As a result, of the many strategies available, delayed production is the learning strategy most often used by students to support students thinking abilities. Students also argue that the strategy is easy to use and makes it easy for them to understand the information they can. In addition, researchers also found one strategy that was less used by students, namely inferencing. Students assume that the strategy is quite difficult to apply in class. According to experts, Inferencing is indeed a strategy that is quite difficult for students to apply so that the strategy is only suitable for adults. Experts believe that in applying inferencing strategy it needs a lot of drills and training in order to help learners apply this strategy in supporting their critical thinking. Keywords: critical thinking, metacognitive strategies, speaking ability, discussion text.